ANALISIS WEBSITE TOKO ONLINE - Prasetya, Andri; Rahmawati, Linda Suvi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
The development of e-commerce has brought changes to the sales strategy of various products in various countries, including Indonesia. Becoming more and more appear various e-commerce website with a variety of offerings including online bookstores. Through observation method perengkingan using machine (Alexa rank & Page rank) of this study wanted to see how much the user knows the website with the keywords typed into the search engine. By using these machines the researchers also wanted to see the world and serve targeted website ranked in Indonesia itself. The results showed that the website tersbut not so well known by the user. This study also showed a high correlation between the name of the site that is easy to remember the number of the arrival of the user.Â Kata Kunci: e-commerce,Â  bookstore